The Emergence of a New Genre: Advertising on the Internet (netvertising) - Fortanet, Immaculada; Palmer, Juan Carlos; Posteguillo, Santiago (HERMES - Journal of Language and Communication in Business, 1999)
This article describes the specific characteristics of internet genres. These genres are characterized by the net system, a specific interlanguage, hypertext, the multimedia effect and an interactive audience. Netvertising is analysed as a representative example of an internet genre. A set of 20 first web pages of banner ads has been studied. The parameters considered are the following ones: http linkers, images used, integration of visuals with text, objectives of the ad, register, audience, overall page length, sentence length, verb tenses, punctuation marks and personal pronouns. Results show that most net ads are short texts. This conciseness is offset by a wider use of other devices such as punctuation marks, images and http linkers. Banner ads are based on an elaboration of images, with the text used, mainly a variety of brief sentences and noun phrases.